Typhoid fever vaccination strategies. (19th June 2015) - Date, Kashmira A.; Bentsi-Enchill, Adwoa; Marks, Florian; Fox, Kimberley
Highlights: Currently available typhoid vaccines have been used in field research and program settings. Several disease control and vaccine delivery strategies are effective and feasible. Selection of strategies depends on the epidemiological and operational contexts. Operational studies with the typhoid conjugate vaccine are needed. Typhoid vaccination should be complemented by improved water, sanitation and hygiene. Abstract: Typhoid vaccination is an important component of typhoid fever prevention and control, and is recommended for public health programmatic use in both endemic and outbreak settings. We reviewed experiences with various vaccination strategies using the currently available typhoid vaccines (injectable Vi polysaccharide vaccine [ViPS], oral Ty21a vaccine, and injectable typhoid conjugate vaccine [TCV]). We assessed the rationale, acceptability, effectiveness, impact and implementation lessons of these strategies to inform effective typhoid vaccination strategies for the future. Vaccination strategies were categorized by vaccine disease control strategy (preemptive use for endemic disease or to prevent an outbreak, and reactive use for outbreak control) and vaccine delivery strategy (community-based routine, community-based campaign and school-based). Almost all public health typhoid vaccination programs used ViPS vaccine and have been in countries of Asia, with one example in the Pacific and one experience using the Ty21a vaccine in South America. All vaccination strategies were found to be acceptable, feasible and effective in the settings evaluated; evidence of impact, where available, was strongest in endemic settings and in the short- to medium-term. Vaccination was cost-effective in high-incidence but not low-incidence settings. Experience in disaster and outbreak settings remains limited. TCVs have recently become available and none are WHO-prequalified yet; no program experience with TCVs was found in published literature. Despite the demonstrated success of several typhoid vaccination strategies, typhoid vaccines remain underused. Implementation lessons should be applied to design optimal vaccination strategies using TCVs which have several anticipated advantages, such as potential for use in infant immunization programs and longer duration of protection, over the ViPS and Ty21a vaccines for typhoid prevention and control.